2017
DOI: 10.15587/1729-4061.2017.98135
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simulation model of safety management in the projects for creating sites with mass gathering of people

Abstract: Проведений аналіз проблем безпеки життє-діяльності на об'єктах з масовим перебуван-ням людей (ОМПЛ). Запропоновано модель-схе-му загроз при управлінні проектами створення ОМПЛ. Запропоновано використання та опи-сано принципи ідентифікації загроз ОМПЛ на стадії планування. Запропоновано класифікації складних систем в управлінні проектами та про-грамами системи цивільного захисту. Здійснено порівняльний аналіз методів та алгоритмів щодо використання імітаційного моделювання у про-ектах даного типу Ключові слова:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
(3 reference statements)
0
9
0
2
Order By: Relevance
“…The next equally important preparatory stage of the study is the choice of mathematical tools for the implementation of the tasks, so on the basis of existing scientific studies in the field the methods of economic and mathematical modeling (Korauš et al (2019), Oliinyk, (2018, Valaskova et al, (2018), Zachko et al, (2017)) we chose multidimensional statistics and regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The next equally important preparatory stage of the study is the choice of mathematical tools for the implementation of the tasks, so on the basis of existing scientific studies in the field the methods of economic and mathematical modeling (Korauš et al (2019), Oliinyk, (2018, Valaskova et al, (2018), Zachko et al, (2017)) we chose multidimensional statistics and regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Conducted literary analysis of the advanced studies, methods, methodologies and normatively-legal base [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] countries of European Union, that de-scribe motion of streams of people showed that in the architectonically-building planning mathematical expressions are not used for determining size of evacuation ways and exits, but a normamount of people is used on unit of width of evacuation way. Accordingly, such model describes a human stream as "elementary" streams, parallel rows of people that follow after each other.…”
Section: Methodsmentioning
confidence: 99%
“…Many scientific works have been devoted to the development of new and the improvement of existing methods, models and mechanisms of rescue services management in the system of civil defense of Ukraine. In the works [1][2][3] the ways of solving the scientifically-applied problem of methodological safe-oriented government construction within development of the difficult organizationally-technical systems projects bases on the example of civil defense are presented. They are offer the system model of safety project of building objects mass stay of people that will realize the methodological going near planning of safety project on the conceptual stage of life cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Розробку нових та вдосконалення наявних методів, моделей та механізмів управління рятувальними служ-бами та системою цивільного захисту розглянуто в роботах (Rak, 2013;Zachko, 2017). У цих працях наведено способи рішення науково-прикладної проблеми щодо побудови методологічних основ безпеко-орієнтованого управління проектами розвитку складних організаційно-технічних систем на прикладі цивільного захисту.…”
unclassified